PENGARUH SISTEM SYARIAH TERHADAP MINAT MASYARAKAT NON MUSLIM DALAM BERTRANSAKSI DI BANK SYARIAH INDONESIA - Dwi Rahadini; M Abdurrahman Faqihudin; Vicky F Sanjaya (Universitas Ngudi Waluyo, 2022)
Aim of this research is to know the application of sharia system in Indonesian Sharia Bank, to know public interest in Indonesian Sharia Bank and non-muslim communities in transactions at Indonesian Sharia Bank. The research activity wa carried out at the Indonesian Sharia Bank in the city of Tangerang. The research method used in journal is a questionnaire method. Samples from this study amounted to 40 respondents. Test were statistical performed using Cronbac’h alpha, construck reliability and Average Variance Extrated (AVE). All proposed hypotheses are supported and significant. The conclusion of this study is that the effect of the sharia system on the interests of non-muslim communities has a significant and positive effect on transaction at Indonesian Sharia Bank.